Controlled homo- and copolymerization of propene and 1-undecene catalyzed by post-metallocenes. (September 2015) - Zakrzewska, S.; Komber, H.; Häussler, L.; Miller, S.A.; Nguyen, H.T.H.; Voit, B.; Schulze, U.
Graphical abstract: Highlights: Post-metallocene catalysts were applied for controlled polymerization of 1-olefins. Quasi-living kinetic regime has been found for 1-undecene polymerization. Block-like copolymers incorporating 1-undecene and propene blocks were synthesized. Block-like structure of the copolymers was proved by 13 C NMR, DSC and SEC. Abstract: Homo- and copolymers of propene and 1-undecene were synthesized by controlled olefin polymerization (quasi-living polymerization) using two bis(phenoxyamine) zirconium complexes as catalysts. The controlled character is demonstrated by an asymptotic growth of molar mass as a function of polymerization time. For the first time, it was possible to synthesize block-like copolymers incorporating long 1-olefins like 1-undecene and propene blocks using the strategy of sequential monomer addition. The obtained copolymers have been characterized in terms of molecular and thermal properties. The copolymer composition was determined by 1 H NMR spectroscopy whereas the quantification of diads by 13 C NMR spectroscopy proves the blocky character of the polymers. SEC results confirm indirectly the formation of block-like copolymers showing monomodal molar mass distribution excluding the formation of two homopolymers. The DSC measurements revealed that the blocky samples show two melting and two crystallization peaks, in contrast to statistical copolymers. These results of DSC and NMR measurements give distinct indication of the blocky type of the copolymer structure.